Glyphosate vulnerability explains changes in root-symbionts propagules viability in Pampean grasslands - Druille, Magdalena (2015)
Research into the impact of agricultural practices on plant symbionts is essential for understanding the factors that modulate plant community productivity and diversity. Although glyphosate is used worldwide as an herbicide, its effects on root symbionts under natural conditions have not been sufficiently studied. We performed a field experiment to evaluate the influence of glyphosate, used for promoting winter forage production, on the viability of arbuscular mycorrhizal fungi (AMF) and rhizobium propagules and other ecosystem traits in native grasslands. The number of viable propagules was strongly reduced with a single application at the recommended dose. Spore viability reduction was dependent on AMF species. Furthermore, changes in plant community composition and soil salinity were detected, which may eventually influence these symbionts in the future. Considering the low nutrient availability and high root-symbiont dependency of several species with forage value, repeated applications might lead to a loss in the grassland diversity and productivity, decreasing livestock production. Application of sublethal doses of this herbicide could avoid these damages, although success in increasing winter forage production would be less. Our results are relevant for understanding the effects of glyphosate on non-target species and designing sustainable land management systems.